Modified α-amylase activity among insecticide-resistant and -susceptible strains of the maize weevil, Sitophilus zeamais - Lopes, K.V.G. (2010)
Fitness cost is usually associated with insecticide resistance and may be mitigated by increased energy accumulation and mobilization. Preliminary evidence in the maize weevil (Coleoptera: Curculionidae) suggested possible involvement of amylases in such phenomenon. Therefore, α-amylases were purified from an insecticide-susceptible and two insecticide-resistant strains (one with fitness cost [resistant cost strain], and the other without it [resistant no-cost strain]). The main α-amylase of each strain was purified by glycogen precipitation and ion-exchange chromatography (≥70-fold purification, ≤19% yield). Single α-amylase bands with the same molecular mass (53.7 kDa) were revealed for each insect strain. Higher activity was obtained at 35–40 °C and at pH 5.0–7.0 for all of the strains. The α-amylase from the resistant no-cost strain exhibited higher activity towards starch and lower inhibition by acarbose and wheat amylase inhibitors. Opposite results were observed for the α-amylase from the resistant cost strain. Although the α-amylase from the resistant cost strain exhibited higher affinity to starch (i.e., lower Km), its Vmax-value was the lowest among the strains, particularly the resistant no-cost strain. Such results provide support for the hypothesis that enhanced α-amylase activity may be playing a major role in mitigating fitness costs associated with insecticide resistance.